The Renewal of Practices: Their Contribution to Strengthening Resilience in Beginning Teachers - Flores-Gomez, C (UNIV NACL, CIDE, 2022)
Purpose. TThis research aims to identify the individual aspects that, added to the pedagogical work and the context in which it is developed, contribute to strengthening teacher resilience in beginning teachers. Method. Regarding methodology, this is a qualitative study of multiple cases that includes eleven beginning high school teachers working in public schools. Interviews and audio messages via the WhatsApp platform were used, which were submitted to content analysis. Results. The results show that the teachers main difficulty is the students low performance, a situation that they face from the renovation of their teaching practices in terms of didactic and evaluative aspects. The teachers interviewed share a positive vision of their students abilities, professional autonomy, a high commitment to student learning, a similar perspective of the meaning of their work, and their social contribution. These shared aspects contribute to a positive bond with peers and the development of collective innovations within collaborative work. Conclusion. The conclusions of the study establish the moral commitment to the teaching of teachers and the contribution of pedagogical innovation in increasing their sense of achievement, as well as the need to generate institutional conditions that allow strengthening the resilience of beginning teachers, providing them with appropriate conditions and opportunities for collaborative teaching work to consolidate professional learning communities.